CONCERN FOR WILD ANIMAL SUFFERING AND ENVIRONMENTAL ETHICS: WHAT ARE THE LIMITS OF THE DISAGREEMENT? - HORTA, OSCAR (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2018)
This paper examines the extent of the opposition between environmentalists and those concerned with wild-animal suffering and considers whether there are any points they may agree on. The paper starts by presenting the reasons to conclude that suffering and premature death prevail over positive well-being in nature. It then explains several ways to intervene in order to aid animals and prevent the harms they suffer, and claims that we should support them. In particular, the paper argues in favour of carrying out more research to learn the best ways to intervene without causing more harm to other animals and to intervene first in areas significantly transformed by human action. It then examines what positions environmentalist views can have towards intervention in nature for the sake of animals. It claims that, while ecocentric and naturocentric views will strongly oppose intervention in certain circumstances, they should not do so in other cases in which the values they promote are not at stake or might be outweighed. The paper then argues that, contrary to what it might seem at first, biocentric views should strongly support intervention. It then discusses whether there may be certain practical issues about which those concerned with wild animal suffering and environmentalists may support the same approach, such as opposition to the greening of desert ecosystems. Finally, it claims that raising awareness about wild animal suffering seems to be the most urgent task now for those concerned about it.